Secure Cloud Storage with Access Control: A Survey - Ranjima, Ms. P; Sumathi, Ms. D; Mathew, Ms.Minimol; Sivaprakash, Mr.P (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is a technique used to refer web based services and development. It is a ubiquitous services, means anyone can access from anywhere in the world at anytime. It provides application, platform and resources to the user. It is a virtualized pool of resources. These services are provided by CSP. The main features of cloud are flexibility, elasticity, on-demand services, metered services, etc. Some large companies offer data storage spaces which are leased to others. So the devices connected to internet can achieve these services. Cloud stores data in database and replicated in different virtual machines, that can be placed anywhere in world. This may leads to some major security issues in cloud storage and retrieval. In order to prevent unauthorized access, access control techniques can be used. A user authentication verifies identity of user. While providing services; we are concern about security and privacy of the information. This survey paper introduces a detailed analysis of security and privacy preserving techniques, and a comparison among various access control mechanism.